Perception and performance of the nursing team in caring for patients with suicide behavior - Silva, Isadora Gabriella Paschoalotto; Lino, Iven Giovanna Trindade; Paiano, Marcelle; Marcon, Sonia Silva; Marquete, Veronica Francisqueti; Batista , Vanessa Carla; Prado, Eleandro do (Acta Scientiarum. Health Sciences, 2022)
Objective: to understand the perception and performance of the Nursing team in a hospital emergency service in the care of patients after attempting suicide. Methods: exploratory study, with a qualitative approach, carried out through semi-structured interviews with Nursing professionals who work in an Emergency Service. The interviews were transcribed and analyzed as to their content following Bardin’s thematic model. Results: seven nurses and four Nursing technicians participated in the study, with an average age of 36 years, most of them female. Suicide attempts are often associated with ‘psychic pain’ that is opposed to the principles of life preservation; such an attitude has caused suicidal behavior to be misinterpreted by health professionals. Conclusion: most professionals demonstrated a stereotyped ‘pre-concept’ and full of taboos about patients who attempted suicide, which triggered a service more directed to physical needs and protocol formalities. Few professionals reported carrying out holistic and empathic care, which is so necessary for these people. In this sense, the importance and urgency of training the team in the identification of suicide risks and in the continuity of treatment of surviving individuals is emphasized.